Estimated functional remnant pancreatic volume predicts nonalcoholic fatty liver disease after pancreaticoduodenectomy: use of computed tomography attenuation value of the pancreas. Issue 5 (May 2021) - Maehira, Hiromitsu; Iida, Hiroya; Maekawa, Takeru; Yasukawa, Daiki; Mori, Haruki; Takebayashi, Katsushi; Kaida, Sachiko; Miyake, Toru; Matsubara, Akiko; Tani, Masaji
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a late complication of pancreaticoduodenectomy (PD). However, this complication is difficult to predict preoperatively. This study aimed to assess the association between NAFLD and preoperative computed tomography (CT) findings. Methods: Medical records of 112 patients who had undergone PD and had CT scans preoperatively and 6 months postoperatively were retrospectively reviewed. We evaluated several CT findings, including the CT attenuation value of the remnant pancreas, remnant pancreatic volume (RPV), and the estimated functional remnant pancreatic volume (eFRPV) on preoperative CT. The variables, including the CT findings and histopathological findings, were compared between the patients with and without NAFLD after PD. Results: The NAFLD group included 21 patients (18.8%). The CT attenuation value of the remnant pancreas was correlated with the pancreatic acinar cell density (r = 0.537), and was lower in the NAFLD group than in the non-NAFLD group (p = 0.007). The eFRPV was lower in the NAFLD group than in the non-NAFLD group (p = 0.002). An eFRPV ≤47 mL·HU was an independent predictive factor for NAFLD (p = 0.007; odds ratio: 6.73; 95% confidence interval: 1.70–26.70). Conclusion: The eFRPV can be used to preoperatively predict NAFLD after PD.